Bees algorithm enhanced with Nelder and Mead method for numerical function optimisation - Kamaruddin, Shafie; Bahari, Muhammad Syahril; Pham, Duc Truong; Mohd Amin Hamzas, Mohd Fidzwan; Zakaria, S (AIP Publishing, 2019)
The Bees Algorithm is a population-based optimisation algorithm inspired by the food foraging behaviour of honey bees. Over the years, this algorithm has been successfully applied to many optimisation problems. In order to enhance its accuracy and convergence rate, it is proposed to employ the Nelder and Mead (NM) method to implement the local search phase of the algorithm. The enhanced algorithm uses directional information to direct recruited bees towards better fitness positions within the local search area. The performance of the proposed algorithm was tested on a set of seventeen well-known benchmark functions. Numerical results show that the proposed algorithm generally performs better than the standard Bees Algorithm.